MARKETING STRATEGIES ANALYSIS OF MILK COW (Case Study in KUD Argopuro, Krucil District, Probolinggo Regency) - B., Bairosi; Miwada, I N.S; Puger, A. W. (Jurnal Peternakan Tropika, 2019)
The aim of this student work practice is to find out the internal and external strategic factors that influence the marketing of milk for dairy cows and to find out the appropriate alternative strategies in the Argopuro Village Cooperative that have a partnership with PT. Nestle Indonesia, Pasuruan. This activity is carried out in Krucil Village during November 2018. This activity uses 55 respondents, consisting of 50 farmers and 5 experts. Respondents of farmers are determined using the random sampling method. Expert respondents were determined using the purposive random sampling method. Data collection is done by direct observation in the field by conducting interviews, and filling out questionnaires. The analytical tool used in this study consisted of EFE Matrix, IFE Matrix, IE Matrix, and SWOT Matrix. SWOT matrix to determine several alternative partnership strategies between KUD Argopuro and PT. Nestle Indonesia, namely by maximizing excellence and opportunities, and minimizing weaknesses and threats. The results of the IFE matrix analysis showed a total score of 3,354 (strong internal position) and the EFE matrix analysis showed a total score of 3,711 (partnership increases profit). The results of this analysis can be concluded that the partnership between KUD Argopuro and PT. Nestle Indonesia, Pasuruan is located in quadrant I, or enters into a growing and nurturing division. This position signifies a strong organization and is in a strong market, so it has a very large strategic opportunity to develop and needs to be maintained. Keywords: KUD Argopuro, Business Partnership, SWOT Analysis